Report of the joint committee on a plan of proceedings to be adopted in the trial of Judge Pitts : March 19, 1862 (Document (Virginia. General Assembly. Senate) ;, 1862)
March 19, 1860 Report of the Joint Committee regarding the course of the proceedings against Judge E.P. Pitts following charges by House of Delegates on February 21, 1862.